Efektivitas Automatic Bike dalam Meningkatkan Kelenturan Sendi Kaki Pada Anak Cerbral Palsy - Fairuz Luthfiyah; Annisa; Ahlul Aulianur; Arisul Mahdi; Grahita Kusumastuti (Universitas Negeri Padang, 2022)
This research is motivated by the problems faced by children with cerebral palsy in the lower limbs -in which children need special services in improving leg joint flexibility- as well as the lack of service innovation for children with cerebral palsy. Services in the form of motion development that can stimulate the leg joints, one of which is by providing treatment using an Automatic bike. This tool uses automatic pedaling and is equipped with an adjustable chair. By using this automatic therapy tool, you can see the effect on the flexibility of a child's feet. This study uses the SSR method to see the results of using the Automatic Bike tool. The results of this study can be seen in the graph of the use of tool in children and this tool can affect the child's lower limbs.